2013
DOI: 10.1021/ja404526x
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-Catalyzed Phosphorylation of Aryl C–H Bonds

Abstract: A Pd(II)-catalyzed C-H phosphorylation reaction has been developed using heterocycle-directed ortho-palladation. Both H-phosphonates and diaryl phosphine oxides are suitable coupling partners for this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
97
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(105 citation statements)
references
References 66 publications
2
97
0
Order By: Relevance
“…[92] t-AmylOH proved to be the best solvent for this reaction. A variety of 2-aryl pyridine substrates were phosphorylated to give the N À P bisdentate compounds which are potentially useful in medicinal chemistry and catalysis.…”
Section: Reviews 224 Phosphorylation Of 2-aryl Pyridinesmentioning
confidence: 96%
See 1 more Smart Citation
“…[92] t-AmylOH proved to be the best solvent for this reaction. A variety of 2-aryl pyridine substrates were phosphorylated to give the N À P bisdentate compounds which are potentially useful in medicinal chemistry and catalysis.…”
Section: Reviews 224 Phosphorylation Of 2-aryl Pyridinesmentioning
confidence: 96%
“…In 2011, Ellman et al developed a Co(III)-catalyzed amidation of 2-aryl pyridines (3) with alkyl/aryl isocyanates (92) to produce the corresponding amide derivatives (93) (Scheme 46). [62] In 2012, Cheng et al also reported a Ru(II)-catalyzed amidation reaction of 2-aryl pyridines (3) with isocyanates (94) via C À H bond activation to obtain the amides (95) in excellent yields (Scheme 47).…”
Section: Amidation Of 2-aryl Pyridinesmentioning
confidence: 99%
“…A pyridine-directed, palladium-catalyzed phosphonylation of C(sp 2 )-H bonds was reported by Murakami et al [125] and Yu et al [126]. A perennial problem in this type of reaction is a strong, competing coordination of phosphorus nucleophiles which may hamper the process of activation of less coordinative C-H bonds.…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…In addition, NMMI was found to be an indispensable reaction component which enabled reductive elimination of the products from the corresponding aryl(phosphonate)Pd(II) complexes. Also, Yu et al [126] developed a catalytic system for C-H phosphonylation of 2-aminoaryl scaffolds, similar to the system shown in Scheme 18. In this instance, the Pd(II)-catalyst deactivation was attenuated by a slow addition of H-phosphonate diesters (ethyl, isopropyl), and p-benzoquinone was used to facilitate the reductive elimination step.…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…Very recently, Yu and co-workers reported a pyridine-directed CÀH phosphonation reaction catalyzed by palladium, in which H-phosphonates were directly used. [5] Expeditious deactivation of the catalyst was avoided by adding H-phosphonate slowly with a syringe pump. Herein, we describe our independent study of the analogous phosphonation reaction of 2-arylpyridines; an ahydroxyalkylphosphonate generates H-phosphonate upon treatment with a base, [6] which serves as the masked phosphonating reagent [7] to save the catalyst from deactivation.…”
mentioning
confidence: 99%